2013
DOI: 10.7845/kjm.2013.3025
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Multidrug Efflux Pump Genes in Enterococci spp. Isolated from Bovine Milk Samples and Their Antibiotic Resistance Patterns

Abstract: The major aim of this study was to investigate the distribution of genes that encode multidrug efflux pumps in Enterococci spp. isolates from bovine milk samples and antibiotic resistance patterns of these strains. of different species of Enterococci, eme(A) was also detected in four strains of E. faecium, seven strains of E. avium, four strains of E. durans and two strains of E. raffinosus. efr(A) was also detected in two strains of E. faecium and two strains of E. durans and efr(B) was also detected in four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
(17 reference statements)
3
2
1
Order By: Relevance
“…Several studies have shown various multidrug efflux pumps in E. faecium, such as efmA, emeA, and efrAB, which are involved in resistance to fluoroquinolones. In this study, the frequency of emeA was 54.5%, which is in agreement with the report published by Jia et al [11] in China, but higher than Kang et al [6] and Sobhanipoor et al [37] in Korea and Iran, respectively. Also, the frequency of efrA/efrB was 51%, which is higher than those reported by Kang et al [6], Sobhanipoor et al [37], and Valenzuela et al [38] in Korea, Iran, and Spain, respectively and lower than the report published by Jabbari et al [39] in Iran.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Several studies have shown various multidrug efflux pumps in E. faecium, such as efmA, emeA, and efrAB, which are involved in resistance to fluoroquinolones. In this study, the frequency of emeA was 54.5%, which is in agreement with the report published by Jia et al [11] in China, but higher than Kang et al [6] and Sobhanipoor et al [37] in Korea and Iran, respectively. Also, the frequency of efrA/efrB was 51%, which is higher than those reported by Kang et al [6], Sobhanipoor et al [37], and Valenzuela et al [38] in Korea, Iran, and Spain, respectively and lower than the report published by Jabbari et al [39] in Iran.…”
Section: Discussionsupporting
confidence: 93%
“…Various mechanisms are involved in the development of resistant strains [3]. Several studies have shown that efflux pumps have become a serious concern for the treatment of infections with multidrug-resistant E. faecium strains [3][4][5][6]. Efflux pumps can not only repel a wide range of antibiotics due to their poly-substance properties but also achieve greater resistance mechanisms by reducing the concentration of intracellular antibiotics and increasing the accumulation of mutations [7].…”
Section: Introductionmentioning
confidence: 99%
“…We also surveyed the existence of efrA and efrB genes in extracted DNA by PCR. The results were higher than in the results of Valenzuela et al's [12] and Kang et al's [32] studies. With the aim to explain that involvement of efrAB in CIP resistance, we investigated that effect of CCCP as an efflux inhibitor on decrease of CIP MIC.…”
Section: Discussioncontrasting
confidence: 68%
“…Additionally, another study found the overexpression in efrAB efflux pump, work as an MDR transporter in Escherichia coli [4]. The other studies has been investigated in fermented or dairy foods [30,43,44]. Our study found one ST847 and two ST480 in E. faecalis isolates.…”
Section: Discussionsupporting
confidence: 56%